E-Government Adoption Success Factors And Their Weight Analysis: A Citizen Perspective - Al-Ani, Mustafa Ayad Anwer; Abdollah, Mohd Faizal; Zakaria, Nurul Azma (JATIT & LLS, 2019)
Since there are many theories, models and factors to choose when investigating the e-government adoption, the issue of how to choose the appropriate factors arises. Hence, this study’s purpose is to overcome this issue by highlighting e-government adoption success variables by performing a weight analysis of the variables relationships. Data were gathered from 141 studies associated to the e-government adoption. Out of those 141 studies, only 94 utilized a variety of constructs with appropriate values of correlation that are required to perform a weight analysis. Both non-significant and significant relationships from all 94 publications are also presented in a diagram. Our findings shows that 15 independent variables were found to be categorized as best predictors, 7 independent variables were found to be categorized as promising predictors, and 12 independent variables were found to be categorized as least effective predictors. This paper contributes by implementing an up to date variables weight analysis, moreover it contributes theoretically to the literature body of e-government and suggests further future work directions.